A case of linear scleroderma "en coup de sabre" with strabismus fixus in a child. (2nd October 2019) - Sen, Pradhnya; Ramawat, Easha; Mohan, Amit; Shah, Chintan
ABSTRACT: Scleroderma, "en coup de sabre" is a rare disorder, characterized by linear depressed scarring at frontoparietal area of the face, seldom associated with ophthalmological findings. Extraocular muscle involvement and paralytic strabismus are rarely associated with linear scleroderma. Here we are reporting a case of unilateral linear scleroderma in an 8-year-old child, with features of strabismus fixus secondary to fibrosed medial rectus (MR) muscle, enophthalmos and en coup de saber (sword-like scar) on the eyebrow. MRI orbit was suggestive of the bulky MR and the inferior rectus muscle. MR recession along with partial loop myopexy resulted in cosmetically acceptable ocular alignment in this case. Histopathology of the portion of muscle and intermuscular septum showed diffuse fibrosis of the muscle. Linear scleroderma may be the causative etiology of strabismus fixus in our case, never reported before in literature.